(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to examine the influence of interactional justice and procedural justice on organizational commitment with perceived organizational support as an intervening variable. The instrument in this research uses a questionnaire in the form of a closed statement because there are already alternative answers in the form of a 1-5 Likert scale, respondents are permanent employees of PT. PLN UP3 Malang (Persero) numbering 106 people. Data analysis uses the help of Smart PLS4 data processing software. The research results show that interactional justice and procedural justice have a significant positive influence on organizational commitment. Perceived organizational support has also been proven to act as an intervening variable that strengthens the relationship between interactional justice, procedural justice, and organizational commitment. This research is useful in the field of human resource management, especially in managing company policy direction by considering aspects of justice and organizational support so that it can increase organizational commitment from employees. This study makes a new contribution by identifying the role of perceived organizational support as an intervening variable in the relationship between interactional justice, procedural justice, and organizational commitment, which can enrich the human resource management literature.